TOTAL FLAVONOID CONTENT ANALYSIS FOUR ILER ACCESSIONS (COLEUS ATROPURPUREUS [L] BENTH) ON LOWLAND KARANGANYAR, CENTRAL JAVA, INDONESIA - FITRIA ROVIQOWATI; YULI WIDIYASTUTI; SAMANHUDI; AHMAD YUNUS (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Iler is an ornamental plant that can be used as a medicinal plant. An effort to increase the flavonoids content was done by planting Iler in the lowlands with the hope that it can increase the secondary metabolites contained to meet the needs of flavonoids obtained from nature. Methods: This research was conducted in Tegal Gedhe Village, Karanganyar Regency with an altitude of 182 m above sea level with Brown Mediterranean soil types. The study used a completely randomized block design. The treatment used consists of one factor which was four accessions of iler plants. Analysis of iler extract was done using ethanol, while analysis of thin layer chromatography (TLC) used the n-hexane:ethyl acetate (6:4) and analysis of total flavonoid were used the AlCl3 method using a spectrophotometer. Results: The total extract content of iler plant in this study was not significantly different, which was accession 1 by 4.009% (±0.36), accession 2 by 5.677% (±0.25), accession 3 by 6.892% (±0.83), and accession 4 by 5.913% (±0.57). TLC analysis shows that accession 1 and accession 2 had 8 spots, while accession 3 and accession 4 formed 9 spots. The highest total flavonoid content was found in accession 2 (5.848% [±0.25]). Conclusion: Accession 2 has a better morphology such as wider leaves characterized by higher source of flavonoids and longer vegetative life than the other three accessions.